Diseñno y fabricación de una silla de ruedas Bipedestadora multi postura con sistema de desplazamiento horizontal y vertical para la empresa Sayan. - Endara Andagua, Willian Fabian (2023)
This thesis presents the design, construction and implementation of a multi-stance standing electric wheelchair with a horizontal and vertical movement system for the company SAY ANI. For this reason, an investigation of scientific reviews of recent years was carried out in the area of technological development of biometric ergonomics in wheelchairs, as well as the advance in technologies in standing devices. Subsequently, a reliable system is designed, composed of a parallelogram mechanism and linear motors, which will allow a standing position to be achieved, forming an angle of 70 degrees. This design was also carried out through a static and dynamic analysis of the wheelchair structure. The movement and movement is independent, due to the use of special motors, the maneuverability and precise control of the movement will be carried out by a control lever or joystick, thus the wheelchair will have optimal performance. The results obtained with the implementation of this mechanical device, it was possible to verify its functionality, stability, mobility, control, precision in the movements that they give the user when changing position with just the press of a button and performing horizontal and vertical movements without getting out of the wheelchair, with greater safety. By considering this design and implementation of an electric standing wheelchair, injuries to the user can be considerably reduced, thus providing them with greater comfort, an advantage in their daily development, work, family. , health, that is, they will help you improve your lifestyle part.